Belarusian literature of 11th–21st centuries: establishment and evolution of genres - Sinkova, Lyudmila D. (Journal of the Belarusian State University. Philology, 2024)
The article describes the research on the problem of the movement of genre forms in domestic artistic writing carried out by scientists of the department of history of Belarusian literature of the faculty of philology of the Belarusian State University in 2023. Genre processes in the texts of Old Belarusian oratorical prose of the 12th–13th centuries, literary monuments of the 16th – beginning of the 17th centuries, genre syncretism in polemical works of the end of the 16th – the first half of the 17th centuries are highlighted, innovations in the genre system of Belarusian poetry and prose of the 19th and 20th– 21st centuries are characterised. The prospects for comparative and semiotic research of genre canons and their modifications in modern domestic literary criticism are outlined.